Community with a shared future for mankind, and how this concept is related to the Belt and road initiative - Chuvilov, Ivan A.; Malevich, Julianna I. (Journal of the Belarusian State University. International Relations, 2022)
China’s foreign policy initiatives have been influential in the evolution of the present world order and multipolar system of international relations. In the second decade of the 21st century, China put forward the concept of a community with a shared future (later succeeded by the notion of a community with a shared future for mankind) and announced its Belt and road initiative. In this study we examine how both are related, and intersect in the humanitarian sphere. We propose an interpretation of a community with a shared future for mankind as a notion that informs China’s present foreign policy. We also explain how it is related to the Belt and road initiative.